Dampak penganguran, pendidikan, kesehatan, PDRB dan indeks pembangunan manusia terhadap kemiskinan di Indonesia - Aini, Laily Nur; Islamy, Sulaiha Nor (Journal of Economics Research and Policy Studies, 2021)
Poverty is a very complex social problem and one of the main problems faced by the Indonesian nation. This study aims to determine the effect of Unemployment, Education, Economic Growth (GDP), and the Human Development Index on Poverty in Indonesia. The quantitative research method uses panel data analysis with secondary data from the Central Statistics Agency of Indonesia. This study shows that unemployment and education do not affect poverty in Indonesia. The health variable shows that health affects poverty in Indonesia. The GDP variable shows the effect on poverty in Indonesia. The HDI variable shows the effect on poverty in Indonesia.